A membrane electrode for electrochemical hydrogen pump water management and its preparation method and application

By adding grafted amino-based hollow mesoporous silica to the anode catalytic layer of the electrochemical hydrogen pump, the problem of the anode drying of EHC under low humidity conditions was solved, and better water management and proton transport performance were achieved.

CN118335995BActive Publication Date: 2025-04-15CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410372651.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2025-04-15
Estimated Expiration
2044-03-29

AI Technical Summary

Technical Problem

Electrochemical hydrogen pumps (EHCs) are prone to anode drying problems under low relative humidity conditions, resulting in difficulty in transferring protons and affecting equipment performance and life.

Method used

The grafted amino hollow mesoporous silica (HMSN-NH2) is added to the anode catalytic layer, which promotes the transfer of protons through the jump mechanism through its good water retention and acid-base interaction with the Nafion ionomer.

Benefits of technology

Effectively prevent drying on the anode side, alleviate the water flooding on the cathode side in a high humidity environment, and improve the proton transmission capacity of the anode catalytic layer in a low humidity environment, and improve the water management capacity of EHC.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118335995B_ABST
    Figure CN118335995B_ABST
Patent Text Reader

Abstract

The present invention discloses a membrane electrode for water management of an electrochemical hydrogen pump, and a preparation method and application thereof. By adding hollow mesoporous silica grafted with amino groups on the anode side, on the one hand, water flooding on the cathode side caused by electroosmotic migration can be alleviated in a high humidity environment; on the other hand, in a low humidity environment, the good water retention of HMSN‑NH2 can effectively prevent the anode side from drying up. In addition, the amino group forms an acid-base interaction with the sulfonic acid group in the Nafion ionomer, which promotes the transfer of protons through a hopping mechanism, greatly improving the proton transport capacity of the anode catalyst layer under low humidity. In general, the membrane electrode is beneficial to the water management ability of the EHC under different operating humidities. The method of the present invention is simple and convenient to operate, and has strong practicality. The prepared membrane electrode exhibits good performance after being assembled into an EHC.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of membrane electrodes, and in particular relates to a membrane electrode for electrochemical hydrogen pump water management, a preparation method and an application thereof. Background Art

[0002] Hydrogen has attracted much attention as an efficient and clean energy source, but due to its low energy density, it is usually used in a compressed form. Electrochemical hydrogen pumps (EHCs) have attracted much attention due to their advantages over mechanical compressors, such as no moving parts, simple structure, fast compression speed, and high efficiency. However, their electrochemical reaction characteristics make them prone to anode dry-out, especially under low relative humidity conditions. This dry-out will cause difficulties in proton transfer in the membrane electrode, which will seriously affect the performance and life of the EHC.

[0003] Due to the high cost and low proton conductivity of PFSA under high temperature (>80°C) and low humidity (<30%) conditions, some research is devoted to the development of new hydrocarbon membranes because of their advantages of low permeability, high thermal stability and low cost. For example, the modification of SPEEK membrane with kaolin nanotubes (HNT) impregnated with phosphotungstic acid can improve the proton conductivity and low humidity performance of the membrane. In addition, there are water management membranes composed of carbon particles and polymer solutions, which have good water retention after modification. However, although the modified PEM has good water retention, it cannot completely solve the problem of uneven water distribution.

[0004] In addition, some schemes improve the water retention performance of membrane electrodes at low humidity by adding hydrophilic materials on the cathode side. For example, Fe-NSC catalyst is used as a hydrophilic material and Pt-C is prepared into a MEA with a double-catalyst layer at the cathode by using a catalyst spraying film method. At 20% RH, the double-layer catalyst layer shows higher power density and stability than the single-layer Pt / C. However, in EHC, the process of proton transfer from the anode to the cathode is designed to be carried out by an on-board mechanism. During this process, protons transfer water from the anode side to the cathode in the form of hydrated protons, resulting in uneven water distribution. When the cathode is hydrophilic, the on-board mechanism and good hydrophilicity can easily cause flooding on the cathode side under high humidity. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and to briefly introduce some preferred embodiments.

[0006] As one aspect of the present invention, the present invention provides a membrane electrode for electrochemical hydrogen pump water management, wherein: in the membrane electrode, hollow mesoporous silica grafted with amino groups is added to the anode catalyst layer.

[0007] As a preferred solution of the membrane electrode for electrochemical hydrogen pump water management described in the present invention: in the anode catalyst layer, the added amount of the hollow mesoporous silica grafted with amino groups is 1wt% to 5wt%.

[0008] As a preferred solution of the membrane electrode for electrochemical hydrogen pump water management described in the present invention: comprising:

[0009] (1) Preparing hollow mesoporous silica grafted with amino groups: adding hexadecyltrimethylammonium bromide and alkali solution to an ethanol aqueous solution for dissolution, adding tetraethoxysilane for reaction, adding the colloid solution obtained by the reaction to an organic solvent for precipitation, dispersing the precipitate in the organic solvent, ultrasonically treating, centrifuging to obtain a white precipitate, drying to obtain a white powder, adding the white powder to an organic solvent, adding (3-aminopropyl)triethoxysilane dropwise, heating for reaction, and obtaining hollow mesoporous silica grafted with amino groups;

[0010] (2) Preparation of membrane electrode: adding the hollow mesoporous silica grafted with amino groups into the anode catalyst layer, and assembling the membrane electrode with a proton exchange membrane, a cathode catalyst layer, and an anode catalyst layer gas diffusion layer.

[0011] As a preferred embodiment of the membrane electrode for electrochemical hydrogen pump water management described in the present invention: in step (1), the solvent includes ethanol; the tetraethoxysilane is added for reaction at a temperature of 30 to 70°C and a reaction time of 3 to 10 hours.

[0012] As a preferred solution of the membrane electrode for electrochemical hydrogen pump water management described in the present invention: in step (1), the (3-aminopropyl)triethoxysilane is added and heated to react at a temperature of 60 to 80° C. for 5 to 15 hours.

[0013] As a preferred solution of the membrane electrode for electrochemical hydrogen pump water management described in the present invention: in step (1), the concentration of the ethanol aqueous solution is 30-50%.

[0014] As a preferred embodiment of the membrane electrode for electrochemical hydrogen pump water management described in the present invention: in step (1), the molar ratio of tetraethoxysilane, hexadecyltrimethylammonium bromide and (3-aminopropyl)triethoxysilane is 1:15-30:5-20.

[0015] As a preferred embodiment of the membrane electrode for electrochemical hydrogen pump water management described in the present invention: in step (2), the mass proportion of the hollow mesoporous silica grafted with amino groups in the anode catalyst layer is 2-3%.

[0016] As a preferred embodiment of the membrane electrode for electrochemical hydrogen pump water management described in the present invention: in step (2), the method for preparing the anode catalyst layer includes mixing Nafion solution, Pt / C catalyst, hollow mesoporous silica grafted with amino groups, organic solvent and water as a slurry, and spraying the slurry onto one side of the proton exchange membrane as the anode catalyst layer.

[0017] Beneficial effects of the present invention: The present invention prepares a membrane electrode for good water management of EHC. By adding hollow mesoporous silica grafted with amino groups on the anode side, on the one hand, the flooding of the cathode side caused by electroosmotic migration can be alleviated in a high humidity environment; on the other hand, in a low humidity environment, the good water retention of HMSN-NH2 can effectively prevent the anode side from drying up. In addition, the amino group forms an acid-base interaction with the sulfonic acid group in the Nafion ionomer, which promotes the transfer of protons through a hopping mechanism, greatly improving the proton transport capacity of the anode catalyst layer under low humidity. In general, the membrane electrode is beneficial to the water management ability of EHC under different operating humidities. The method of the present invention is simple and convenient to operate, and has strong practicality. The prepared membrane electrode exhibits good performance after being assembled into an EHC. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment, wherein:

[0019] Figure 1 FT-IR spectrum and nitrogen adsorption-desorption isotherm of HMSN-NH2.

[0020] Figure 2 Contact angle and water absorption of traditional Pt / C and adding different types of HMSN catalytic layers.

[0021] Figure 3 EIS curves of traditional Pt / C and different types of HMSN catalyst layers under H2-N2 at 50% RH.

[0022] Figure 4 Compression curves and CV curves of membrane electrodes with traditional Pt / C anode and different types of HMSN added at 100% RH.

[0023] Figure 5 Compression curves and CV curves of membrane electrodes with traditional Pt / C anode and different types of HMSN added at 50% RH.

[0024] Figure 6 Adding different types of HMSN membrane electrodes to traditional Pt / C and anode at 50% RH at 0.5A / cm 2 EIS curves at different current densities.

[0025] Figure 7 The compression curves at 100% RH and 50% RH were tested under H2-Air conditions when 2.5% mass fraction of HMSN-NH2 was added to the anode, cathode and proton exchange membrane, respectively. DETAILED DESCRIPTION

[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0027] A membrane electrode with a hollow mesoporous silica grafted with amino groups on the anode side catalyst layer was prepared, which effectively alleviated the anode drying during operation and showed good compression and polarization properties in EHC.

[0028] Embodiment 1:

[0029] Synthesis method of hollow mesoporous silica grafted with amino groups (HMSN-NH2): 4 g hexadecyl trimethyl ammonium bromide and 1 mL ammonia water (Aladdin, 30%) were added to a mixture of 30 mL anhydrous ethanol and 60 mL deionized water, heated to 50 ° C in a water bath and stirred continuously. When the solid was completely dissolved, 0.3 mL tetraethoxysilane was added, the temperature was stabilized at 30 ° C and stirred for 5 h, the colloidal solution obtained after the reaction was centrifuged with anhydrous ethanol to collect the precipitate, then dispersed in anhydrous ethanol, and ultrasonicated for 2 h (60 kHz). After that, the ultrasonic product was centrifuged to obtain a white precipitate, which was dried in a vacuum oven at 80 ° C for 6 h and ground to obtain a white powder. 1.5 g of the obtained white powder was added to 50 mL anhydrous ethanol, and 3 mL (3-aminopropyl) triethoxysilane was dripped, then the temperature was raised to 80 ° C and refluxed for 10 h, and finally dried in a vacuum oven at 80 ° C for 5 h, and the product HMSN-NH2 was obtained by grinding.

[0030] Comparative Example 1:

[0031] Synthesis method of hollow mesoporous silica grafted with carboxyl groups (HMSN-COOH): 4 g of hexadecyltrimethylammonium bromide and 1 mL of ammonia water (Aladdin, 30%) were added to a mixture of 30 mL of anhydrous ethanol and 60 mL of deionized water, heated to 50 ° C in a water bath and stirred continuously. When the solid was completely dissolved, 0.3 mL of tetraethoxysilane was added, and the temperature was stabilized at 30 ° C and stirred for 5 h. The colloidal solution after the reaction was centrifuged with anhydrous ethanol to collect the precipitate, and then dispersed in anhydrous ethanol and ultrasonicated for 2 h (60 kHz). The ultrasonic product was then centrifuged to obtain a white precipitate, which was dried in a vacuum oven at 80 ° C for 6 h and ground to obtain a white powder. 1.5 g of the obtained white powder was added to 50 mL of deionized water, 1.5 mL of (3-ethoxysilyl)-propyl succinic anhydride was slowly added dropwise, and then 50 mL of 0.1 M HCl was added. The reactants were heated to 50 ° C. and stirred for 5 h. Finally, they were dried in a vacuum oven at 80 ° C. for 5 h and ground to obtain the product HMSN-COOH.

[0032] Comparative Example 2:

[0033] Synthesis method of hollow mesoporous silica (HMSN): Take 4g of hexadecyltrimethylammonium bromide and 1mL of ammonia water (Aladdin, 30%) and add them to a mixed system of 30mL of anhydrous ethanol and 60mL of deionized water, heat them to 50°C in a water bath and stir them continuously. When the solid is completely dissolved, add 0.3mL of tetraethoxysilane, and stir and react at a temperature of 30°C for 5h. The colloidal solution after the reaction is centrifuged with anhydrous ethanol to collect the precipitate, then disperse it in anhydrous ethanol and ultrasonicate it for 2h (60kHz). After that, the ultrasonic product is centrifuged to obtain a white precipitate, which is dried in a vacuum oven at 80°C for 5h and ground to obtain a white powder, which is HMSN.

[0034] Comparative Example 3:

[0035] Preparation of traditional membrane electrode: Platinum loading of 0.4 mg by transfer printing Pt / cm 2 The commercial catalyst layer was hot pressed (150°C) onto one side of the proton exchange membrane (Nafion211), recorded as the cathode catalyst layer. Take 54μL Nafion solution (D2020), add 20mg Pt / C (50%), then drop 896μL isopropanol solution and 703μL deionized water to make the anode catalyst layer slurry. The slurry was ultrasonicated (60kHz) in an ice bath for 20min, and sprayed onto the other side of the membrane (area 2cm×2cm) as the anode catalyst layer. When the loading reached 0.15mg Pt / cm 2 Then the spraying was stopped, and then the gas diffusion layer was added to both the cathode and cathode, and the membrane electrode was placed on the graphite bipolar plate using a polytetrafluoroethylene gasket and assembled.

[0036] Comparative Example 4:

[0037] Preparation method of membrane electrode with HMSN-COOH added to the anode: Platinum loading of 0.4 mg was transferred Pt / cm 2 The commercial catalyst layer was hot pressed (150°C) onto one side of the proton exchange membrane (Nafion 211), recorded as the cathode catalyst layer. Take 54μL Nafion solution (D2020), add 20mg Pt / C (50%) and 0.76mg HMSN-COOH synthesized in Comparative Example 1 (the mass fraction in the dry catalyst layer is 2.5%), and then drip 896μL isopropanol solution and 703μL deionized water to prepare the anode catalyst layer slurry. Ultrasonicate the slurry in an ice bath (60kHz) for 20min. And spray it to the other side of the membrane (area of ​​2cm×2cm) as the anode catalyst layer. When the loading reaches 0.15mg Pt / cm 2 Then stop spraying, add gas diffusion layers to the cathode and anode, and place the membrane electrode on the graphite bipolar plate using a polytetrafluoroethylene gasket and assemble.

[0038] Comparative Example 5:

[0039] Preparation method of membrane electrode with HMSN added to the anode: Platinum loading of 0.4 mg by transfer printing Pt / cm 2 The commercial catalyst layer was hot pressed (150°C) onto one side of the proton exchange membrane (Nafion 211), recorded as the cathode catalyst layer. Take 54μL Nafion solution (D2020), add 20mg Pt / C (50%) and 0.76mg HMSN synthesized in Comparative Example 2 (the mass fraction in the dry catalyst layer is 2.5%), and then drop 896μL isopropanol solution and 703μL deionized water to prepare the anode catalyst layer slurry. The slurry was ultrasonicated (60kHz) in an ice bath for 20min, and sprayed onto the other side of the membrane (area of ​​2cm×2cm) as the anode catalyst layer. When the loading reached 0.15mg Pt / cm 2 Then stop spraying, add gas diffusion layers to the cathode and anode, and place the membrane electrode on the graphite bipolar plate using a polytetrafluoroethylene gasket and assemble.

[0040] Embodiment 2:

[0041] Preparation method of membrane electrode with HMSN-NH2 added to the anode: Platinum loading of 0.4 mg was transferred Pt / cm 2The commercial catalyst layer was hot pressed (150°C) to one side of the proton exchange membrane (Nafion 211), recorded as the cathode catalyst layer. Take 54μL Nafion solution (D2020), add 20mg Pt / C (50%) and 0.3mg, 0.76mg, and 1.55mg HMSN-NH2 synthesized in Example 1 (the mass fractions in the dry catalyst layer were 1%, 2.5%, and 5%, respectively), and then drop 896μL isopropanol solution and 703μL deionized water to prepare the anode catalyst layer slurry. The slurry was ultrasonicated (60kHz) in an ice bath for 20min, and sprayed to the other side of the proton exchange membrane (area of ​​2cm×2cm) as the anode catalyst layer. When the loading reached 0.15mg Pt / cm 2 Then stop spraying, add gas diffusion layers to the cathode and anode, and place the membrane electrode on the graphite bipolar plate using a polytetrafluoroethylene gasket and assemble.

[0042] Comparative Example 6:

[0043] Nafion membrane preparation method: 1 mL Nafion solution (D2020) was mixed with N, N-dimethylformamide (DMF) solution, and the mass fraction of Nafion was 10%. The obtained solution was dripped onto a glass plate with a pipette and coated with a coater, and the thickness was set to 30 μm. Next, the obtained film was vacuum dried in an oven at 80°C for 12 hours, then cooled to room temperature, moistened with deionized water and slowly peeled off to obtain the desired Nafion membrane.

[0044] Comparative Example 7:

[0045] Preparation method of Nafion membrane with HMSN-NH2 added: 1 mL Nafion solution (D2020) was mixed with N, N-dimethylformamide (DMF) solution, and 0.01 mg HMSN-NH2 synthesized in Example 1 was added at the same time, and the mass fraction of Nafion in the mixed system was 10%. The obtained solution was then dripped onto a glass plate with a pipette and coated with a coater, with a thickness set to 30 μm. Next, the obtained film was vacuum dried in an oven at 80°C for 12 hours, then cooled to room temperature, moistened with deionized water and slowly peeled off to obtain the desired Nafion membrane.

[0046] Comparative Example 8:

[0047] Preparation method of homemade membrane electrode for cathode HMSN-NH2: Take 54μL Nafion solution (D2020), add 20mgPt / C (50%), then drop 896μL isopropanol solution and 703μL deionized water to make anode catalyst layer slurry. Ultrasonicate the slurry in an ice bath (60kHz) for 20min and spray it on one side of the membrane (area 2cm×2cm) as the anode catalyst layer. When the loading reaches 0.15mg Pt / cm 2 Then stop spraying, take 54 μL Nafion solution (D2020), add 20 mg Pt / C (50%) and 0.76 mg HMSN-NH2 synthesized in Example 1 (the mass fraction in the dry catalyst layer is 2.5%), and then drop 896 μL isopropanol solution and 703 μL deionized water to prepare the anode catalyst layer slurry. Ultrasonicate the slurry in an ice bath (60kHz) for 20 minutes. Load the obtained slurry into a spray gun and spray it to the other side of the membrane (area 2cm×2cm) as the cathode catalyst layer. When the loading reaches 0.4 mg Pt / cm 2 Then the spraying is stopped. The membrane electrode is placed on the graphite bipolar plate through a polytetrafluoroethylene gasket for assembly.

[0048] Embodiment 3:

[0049] Preparation method of homemade membrane electrode with HMSN-NH2 added to the anode: Platinum loading of 0.4 mg was transferred Pt / cm 2 The commercial catalytic layer was hot pressed (150°C) to one side of the homemade membrane in Comparative Example 6, recorded as the cathode catalytic layer. Take 54μL Nafion solution (D2020), add 20mg Pt / C (50%) and 0.3mg, 0.76mg, and 1.55mg HMSN-NH2 synthesized in Example 1 (the mass fractions in the dry catalytic layer were 1%, 2.5%, and 5%, respectively), and then drop 896μL isopropanol solution and 703μL deionized water to prepare the anode catalytic layer slurry. Ultrasonicate the slurry in an ice bath (60kHz) for 20min. The obtained slurry was loaded into a spray gun and sprayed to the other side of the homemade membrane (area of ​​2cm×2cm) as the anode catalytic layer. When the loading reaches 0.15mg pt / cm 2 Then stop spraying, add gas diffusion layers to the cathode and anode, and place the membrane electrode on the graphite bipolar plate using a polytetrafluoroethylene gasket and assemble.

[0050] Figure 1 (a) FT-IR spectrum of HMSN-NH2 (b) nitrogen adsorption-desorption isotherm. Figure 1 a, where at 1070cm-1 The strong absorption band at 803cm is caused by the antisymmetric stretching vibration of Si-O-Si group. -1 There is a Si-O stretching vibration absorption band at about 3400 cm -1 There is a broad absorption peak at 3280 and 3373 cm, which can be attributed to the stretching vibration of the silanol group. -1 The two NH stretching vibration peaks at indicate the successful grafting of amino functional groups. The nitrogen adsorption-desorption isotherms of HMSN-NH2 (e.g. Figure 1 b) exhibits a typical IV-type adsorption / desorption pattern, corresponding to the mesoporous structure in the shell. Its specific surface area and pore volume are 155 m 2 / g and 0.34cm 3 / g. The pore size of HMSN-NH2 was 4.1nm obtained by BJH plot, which corresponds to the micelle diameter of CTAB. The above characterizations prove the successful synthesis of hollow mesoporous SiO2 microspheres grafted with carboxyl groups.

[0051] Figure 2 (a) Contact angle (b) Water absorption of conventional Pt / C and catalyst layers with different types of HMSN added. The conventional Pt / C catalyst layer and the catalyst layer with different types of HMSN added were prepared by spraying the catalyst layer slurry in Comparative Examples 3-5 and Example 2 onto a PTFE substrate. The contact angles are shown in FIG. Figure 2 As shown in a. Among them, the hydrophilicity of the catalytic layer with the addition of 2.5% HMSN-NH2 is significantly improved compared with the traditional catalytic layer. In comparison, the contact angles of the catalytic layers with the same amount of HMSN and HMSN-COOH are 100° and 84°, respectively. It can be found that modifying the surface of HMSN with amino functional groups can increase the hydrophilicity of the prepared catalytic layer. However, compared with the amino functional groups, modification with carboxyl groups has a greater improvement in the hydrophilicity of the catalytic layer. The water storage capacity of the catalytic layer is characterized by its water absorption, which is obtained by subtracting the mass of each catalytic layer after being placed in a constant temperature and humidity chamber (50°C, 90% RH) for 12 hours from its mass after drying in an oven at 80°C for 6 hours and dividing it by its surface area. The water absorption of the catalytic layer with different types of HMSN is shown in the figure. Figure 2 As shown in b, it can be found that the change in the water absorption of the catalyst layer is similar to the contact angle, among which the original catalyst layer has the worst water absorption, which is 0.037 mg cm -2 , while the water absorption of the catalyst layer with 2.5% HMSN-NH2, HMSN-COOH and HMSN was 0.069, 0.081 and 0.059 mg cm -2 This indicates that due to the hydrophilicity of the material and the structural characteristics of the hollow mesopores, it can be used as a micro water tank in the catalytic layer, further improving the water storage function of the catalytic layer.

[0052] Figure 3 The EIS curves of traditional Pt / C and different types of HMSN catalyst layers under H2-N2 at 50% RH. The proton transport performance of the catalyst layer was obtained by EIS test under hydrogen-nitrogen conditions, where hydrogen was passed through the cathode side with a flow rate of 0.1slpm; nitrogen was passed through the anode side with a flow rate of 0.1slpm, the humidity was set to 50%, and the back pressure was 2bar. The intercept of the second linear region with the real axis corresponds to R CL (Proton transfer impedance) / 3+R HFR (High frequency impedance). Figure 3 It can be found that the catalyst layer with 2.5% HMSN-NH2 has the smallest R HFR . In low humidity, R HFR This is mainly caused by the change in membrane ionic resistivity caused by the decrease in hydration degree, so the addition of HMSN-NH2 effectively improves the membrane hydration degree. CL It is also less than the catalyst layer with 2.5% HMSN-COOH and HMSN added, which shows that the addition of HMSN-NH2 promotes proton conduction in the catalyst layer well, and the effect is better than HMSN-COOH and HMSN. This performance improvement is attributed to the formation of acid-base pairs between the sulfonic acid groups of the ionomer side chains in the catalyst layer and the amino functional groups in HMSN-NH2. Through this special interaction, an efficient and long-distance proton transport channel is formed. This proton transport mode is less dependent on moisture, so it can effectively improve proton transport in the catalyst layer under low relative humidity conditions.

[0053] Figure 4 (a) Compression curves and (b) CV curves of membrane electrodes with traditional Pt / C anode and different types of HMSN added (Comparative Example 3, Comparative Example 4, Comparative Example 5, Example 2) at 100% RH.

[0054] Figure 4 a is the compression performance of the catalyst layer with different contents of HMSN-NH2 added at 100% RH. The test conditions are 0.3slpm hydrogen passing through the cathode, the humidity is set to 100%, and the back pressure is 2bar. It can be found that the membrane electrode with 2.5% HMSN-NH2 added to the anode has the best compression performance, followed by 2.5% HMSN-COOH, and all membrane electrodes with silicon balls have better performance than traditional membrane electrodes. This is because the hydrophilic anode side is conducive to inhibiting the transport of anode water to the cathode through electroosmosis, while promoting the reverse diffusion of cathode water, effectively improving the flooding of the cathode, and the performance improvement effect of HMSN-COOH with the best water absorption is not as good as HMSN-NH2. It is speculated that this is due to the excessive water absorption that leads to supersaturation of anode water. Figure 4b. From the size of the hydrogenolysis region, it can be found that ECSA has the same trend as the compression performance and polarization performance, indicating that adding different types of HMSN in the catalytic layer is beneficial to expanding the three-phase interface and improving the utilization of the Pt catalyst, among which HMSN-NH2 has the best improvement effect.

[0055] Figure 5 (a) Compression curve and (b) CV curve of membrane electrodes with traditional Pt / C anode and different types of HMSN added (Comparative Example 3, Comparative Example 4, Comparative Example 5, Example 2) at 50% RH.

[0056] The compression curves of membrane electrodes with different types of HMSN added to the anode at 50% RH are shown in Figure 2. Figure 5 a. The test conditions are the same as above, but the humidity is changed to 50%. It can be found that the catalyst layer with 2.5% HMSN-NH2 added in the test exhibits better compression performance, which successfully compresses hydrogen to 0.9MPa within 60 seconds, while the catalyst layers with 2.5% HMSN and HMSN-COOH added require 109 seconds and 69 seconds respectively to compress hydrogen to the same pressure. This is because the amino group of HMSN-NH2 forms an acid-base pair with the sulfonic acid group of Nafion, enriching the proton transport pathway under low humidity and promoting the transfer of protons from the anode to the cathode. In addition, the traditional membrane electrode requires 134 seconds to compress hydrogen to 0.85Mpa, which is attributed to its poor water absorption performance under low humidity, resulting in the inability to form sufficient proton transport channels. The CV curves of different catalytic layers are shown in Figure 2. Figure 5 b. Also at 50% RH, adding different types of HMSN into the catalyst layer increased the electrochemical active area, and adding HMSN-NH2 had the best effect.

[0057] Figure 6 Adding different types of HMSN membrane electrodes to traditional Pt / C and anode at 50% RH at 0.5A / cm 2 EIS curves at different current densities.

[0058] EIS of traditional Pt / C and membrane electrodes with different types of HMSN added Figure 6 During the test, the anode maintained a hydrogen flow rate of 0.3slpm and the current was set to 0.5A / cm 2 The horizontal coordinate of the intersection of the arc and the real axis is the ohmic impedance (R Ω ), under low humidity conditions, its size is mainly affected by proton conduction in the PEM. Ω It can be found that the conventional Pt / C catalyst layer assembled membrane electrode has a much higher R than other MEAs at 50% RH. Ω, which indicates that the introduction of hydrophilic materials in the anode CL can greatly improve the proton conduction in the membrane through water retention under low humidity. In addition, it can be found that the membrane electrode with 2.5% HMSN-NH2 added at the anode has the smallest R Ω This is because the acid-base pair formed by the amino group and the sulfonic acid group in the catalytic layer can realize long-distance and low-energy barrier proton transport, which is more advantageous than conducting protons through the on-board mechanism or traditional hopping mechanism.

[0059] Figure 7 HMSN-NH2 with a mass fraction of 2.5% was added to the anode, cathode and proton exchange membrane respectively (Comparative Example 7, Comparative Example 8, Example 3) and tested under H2-Air conditions: (a) compression curve at 100% RH and (b) compression curve at 50% RH.

[0060] When the EHC is in operation, due to electroosmotic migration, the anode is prone to drying up and the cathode is flooded. Therefore, the water management of the EHC membrane electrode is often focused on promoting drainage on the cathode side or hydrophilicity on the anode side. If the hydrophilic filler HMSN-NH2 is added to the cathode side, it may aggravate the flooding of the membrane electrode. Similarly, if the membrane is hydrophilic, although it can also promote the hydration of the membrane under low humidity and reduce the proton transfer resistance, the performance improvement is relatively limited because the drying up of the anode side cannot be fully resolved. In order to verify the above inference, Figure 7 a shows the comparison of the compression performance of the membrane electrode when HMSN-NH2 is doped into the cathode catalyst layer, the anode catalyst layer and the membrane respectively at 100% RH. It can be found that after adding HMSN-NH2 to the cathode, it takes 87s to compress H2 to 0.85MPa, and the performance is significantly weaker than that of the membrane electrode doped into the anode and the membrane. This is because the cathode is very prone to flooding under high humidity, and the high hydrophilicity will cause the liquid water to be unable to be discharged in time, and the addition into the membrane is also prone to cause liquid water accumulation; on the contrary, the hydrophilic modification of the anode side can promote more protons to complete the transmission through the hopping mechanism, and prevent a large amount of water from migrating to the cathode side by inhibiting electroosmotic migration, so it has better compression performance. Figure 7 b shows the compression performance of the above membrane electrode at 50% RH. Similarly, adding HMSN-NH2 to the anode side not only improves its hydrophilicity, but also the acid-base interaction between the amino group and the sulfonic acid group provides an efficient channel for the long-distance transport of protons. Therefore, the membrane electrode exhibits the best compression performance. Adding HMSN-NH2 to the cathode or the membrane cannot provide sufficient improvement for the drying of the anode side, so the compression performance is poor.

[0061] In summary, we have prepared a membrane electrode for good water management of EHC. By adding hollow mesoporous silica grafted with amino groups on the anode side, on the one hand, it can alleviate the flooding of the cathode side caused by electroosmotic migration in a high humidity environment; on the other hand, in a low humidity environment, the good water retention of HMSN-NH2 can effectively prevent the anode side from drying up. In addition, the amino groups form acid-base interactions with the sulfonic acid groups in the Nafion ionomer, which promotes the transfer of protons through a hopping mechanism, greatly improving the proton transport capacity of the anode catalyst layer under low humidity. In general, this membrane electrode is beneficial to the water management ability of EHC under different operating humidity.

[0062] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a membrane electrode for electrochemical hydrogen pump water management, characterized in that: include, (1) Preparation of hollow mesoporous silica grafted with amino groups: adding hexadecyltrimethylammonium bromide and alkali solution to an ethanol aqueous solution for dissolution, adding tetraethoxysilane for reaction, adding the colloidal solution obtained by the reaction to ethanol for precipitation, dispersing the precipitate in ethanol, ultrasonically treating, centrifuging to obtain a white precipitate, drying to obtain a white powder, adding the white powder to an organic solvent, adding (3-aminopropyl)triethoxysilane dropwise, heating for reaction, and obtaining hollow mesoporous silica grafted with amino groups; (2) preparing a membrane electrode: adding the hollow mesoporous silica grafted with amino groups to an anode catalyst layer, and assembling a membrane electrode using a proton exchange membrane, a cathode catalyst layer, and an anode catalyst layer gas diffusion layer; In step (1), the tetraethoxysilane is added for reaction at a temperature of 30-70°C for a reaction time of 3-10 hours; the (3-aminopropyl)triethoxysilane is added dropwise for heating reaction at a temperature of 80°C for 10 hours; the concentration of the ethanol aqueous solution is 30-50%; The molar ratio of tetraethoxysilane, hexadecyltrimethylammonium bromide and (3-aminopropyl)triethoxysilane is 1:15~30:5~20; In step (2), the mass proportion of the hollow mesoporous silica grafted with amino groups in the anode catalyst layer is 2-3%.

2. The method for preparing a membrane electrode for electrochemical hydrogen pump water management according to claim 1, characterized in that: In step (2), the method for preparing the anode catalyst layer comprises mixing Nafion solution, Pt / C catalyst, hollow mesoporous silica grafted with amino groups, organic solvent and water as slurry, and spraying the slurry onto one side of the proton exchange membrane as the anode catalyst layer.

3. Application of the membrane electrode prepared by the preparation method of the membrane electrode for electrochemical hydrogen pump water management according to claim 1 in electrochemical hydrogen pump water management.

Citation Information

Patent Citations

  • Mesoporous silica fine particles, method for producing mesoporous silica fine particles, mesoporous silica fine particle-containing composition, mesoporous silica fine particle-containing molding material, and organic electroluminescence element

    CN103781726A

  • Membrane electrode and preparation method and application thereof

    CN117476986A